ANALISIS PERAN PENYULUH PERTANIAN DALAM PENINGKATAN KOMPETENSI PETANI DALAM RANGKA PENINGKATAN MUTU KOPI ARABIKA DI KABUPATEN KERINCI - Erian Eka Pranata; Gunarif Taib; Asmawi Asmawi (Agros Journal of Agriculture Science, 2023)
Agricultural extension workers have an important role in improving the skills and knowledge of farmers. In Kerinci Regency there is an Arabica coffee agricultural sector which is still lacking in development, for this reason this research was conducted with the aim of analyzing the role of agricultural extension workers in increasing the competence of farmers in order to improve the quality of Arabica coffee and analyzing the obstacles faced by extension agents in improving the quality of Arabica coffee in Kerinci Regency . This study used mixed methods, namely a combination of quantitative and qualitative methods. The results of this study found that the role of agricultural extension as a motivator was moderate, the role of extension agents as educators was not good, the role of extension agents as disminators was not good, the role of extension agents as facilitators was very good and the role of extension officers as organizers was moderate. The constraints faced by agricultural extension workers in Kerinci Regency are technical; Extension agents are constrained by quality seeds, lack of knowledge of the extension personnel themselves, availability of seeds, lack of knowledge of farmers, and from a marketing perspective, the limited availability of quality Arabica coffee.INTISARIPenyuluh pertanian memiliki peranan penting dalam peningkatan keterampilan dan pengetahuan petani. Di Kabupaten Kerinci terdapat sektor pertanian kopi Arabika yang masih kurang dalam pengembangannya, untuk itu dilakukan penelitian ini dengan tujuan menganalisis peran penyuluh pertanian dalam peningkatan kompetensi petani dalam rangka peningkatan mutu kopi arabika serta menganalisis kendala yang dihadapi oleh penyuluh dalam meningkatkan mutu kopi arabika di Kabupaten Kerinci. Penelitian ini menggunakan metode campuran (mix methods) yaitu penggabungan antara metode kuantitatif dan kualitatif. Hasil dari penelitian ini didapatkan bahwasanya peran penyuluh pertanian sebagai motivator yaitu sedang, peran penyuluh sebagai edukator kurang baik, peran penyuluh sebagai diseminator kurang baik, peran penyuluh sebagai fasilitator sangat baik dan peran penyuluh sebagai organisator sedang. Kendala yang dihadapi oleh penyuluh pertanian di Kabupaten Kerinci adalah secara teknis; penyuluh terkendala bibit yang bermutu, kurangnya pengetahuan SDM penyuluh itu sendiri, ketersediaan bibit, kurangnya pengetahuan petani, serta dari segi pemasaran adalah keterbatasan ketersediaan kopi arabika yang berkualitas.